Gender inequalities in extended working life: a systematic review of qualitative studies - Francisca Ortiz Ruiz; Ignacio Cabib; Andrés Biehl; Carlos Budnevich-Portales; Trinidad Cereceda; Juan Pablo Ormeño; Martina Yopo-Díaz (International Journal of Ageing and Later Life)
Extended working life (EWL) in old age is an increasingly prevalent phenomenon in aging populations. Gender inequalities constitute one of the most studied aspects of EWL. However, research on this issue has been predominantly quantitative, resulting in limited understanding of the situated meanings and experiences of work in old age for men and women. This article sheds light on the few studies that have explored gender inequalities in EWL qualitatively, systematically reviewing 47 articles. This study includes a meta-analysis of the papers reviewed, discusses the most frequent topics and content addressed by qualitative studies, and introduces a brief overview of the main findings on gender inequalities in the literature. These findings underscore that the literature has mainly been published in countries of the Global North, with data primarily focused on those nations. Additionally, there is an emphasis on research related to the meanings, decisions, policies, and narratives surrounding retirement, while only a limited number of articles have a defined theoretical framework. Finally, the limited number of comparisons between countries suggests a need for further research from these perspectives. We conclude this systematic review by discussing the main findings, suggesting policy implications of our work and identifying gaps that should be addressed in future research.